2011
DOI: 10.1007/s11999-010-1452-z
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Bifid Iliopsoas Tendon Causing Refractory Internal Snapping Hip

Abstract: Background Treatment of painful internal snapping hip (coxa saltans) via arthroscopic lengthening or release of the iliopsoas tendon is becoming preferred over open tech-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
(29 reference statements)
0
38
0
4
Order By: Relevance
“…[2][3][4][5][6][7][8][9] Anderson and Keene 2 studied a series of 15 athletes treated for ISHS with endoscopic release at the level of the lesser trochanter. None of the patients had recurrent snapping or pain in the hip at 3, 6, or 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9] Anderson and Keene 2 studied a series of 15 athletes treated for ISHS with endoscopic release at the level of the lesser trochanter. None of the patients had recurrent snapping or pain in the hip at 3, 6, or 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Revision surgery was successful by releasing the remaining tendon. 6 Deslandes et al 4 reported on 18 patients with painful internal snapping hips. Two patients were found to have bifid tendons; in 1 patient the phenomenon was bilateral, which was discovered by retrospective review of dynamic ultrasound recordings of the snapping phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the iliopsoas tendon is described as a conjoined tendon of the psoas major (originating from the transverse process of the lumbar vertebrae) and iliacus muscles (originating from the upper two-thirds of the iliac fossa and inner lip of the iliac crest) with insertion on the lesser trochanter. 21,22 This particular muscle group is often implicated in hip flexion, 23 including movements such as kicking and running, and thus the prevalence of iliopsoas injury is observed to be highest among soccer players and running athletes. 16 However, it can also be a cause of groin pain in the ice hockey player because the iliopsoas is also implicated in lumbar posture and pelvic control.…”
Section: Hip Flexor Muscle Injury and Iliopsoas Tendinitismentioning
confidence: 99%
“…However the tendon could be bifid as reported by Shu et al in 2011, during revision arthroscopy. 13 The psoas tendon lies lateral to the femoral artery, while the iliopsoas bursa lies between the musculotendinous junction and the pelvic brim. 11 Hence the psoas tendon is easily palpable lateral to the femoral artery pulsations.…”
Section: Gross Anatomymentioning
confidence: 99%